STRUCTURAL ORDER AND PHASE FORMATION OF THE SUPERCONDUCTOR LaCaBaCu2.8(X)0.2(O)7-δ WITH X= (P04)^(3-) AND (B03)^(3-) - De Los Santos V., Luis (2007)
The LaCaBaCu2.80(X)0.20(O)7-δ compound with X=(P04)^(3-) and (BO3)^(3-) has been prepared by a solid state reaction method and we compare the resulting structures. phase formation and CriticaL Temperatures (Tc's) with the well known LaCaBaCu3(O)7-δ (La1113) superconductor. For both cases, the X-ray diffractogram revealed the BaCuO2 and CuO as extra phases; this is confirmed by SEM, EDX and HAEM. The Rietveld analysis suggested orthorhombic crystalline structures belonging to the Pmmm spatial group with a=3.849Å, b=3.880Å and c=11.630Å to the LaCaBaCu2.80(P04)0.20(O)7-δ, and a=3.884Å b=3.890Å and C=11.640Å to the LaCaBaCu2.80(BO3)0.20(O)7-δ. Tc's were calculated from the derivativa of magnetic susceptibility plots by using a SQUID detection system, these indicated the Tc's are 86K and 55K to the LaCaBaCu2.80(P04)0.20(O)7-δ and the LaCaBaCu2.80(BO3)0.20(O)7-δ respectively.